ENT 530 Case Study: Aducktive / Muhammad Khairul Taqwa Mohamad ... [et al.] - Mohamad, Muhammad Khairul Taqwa; Abdul Rahman, Imran Rakin; Omar Suhaimi, Shahrul Naim; Komilus, Aarol Cay; Sarjani, Ahmad Zaki (2021)
Aducktive is a beverages brand that sells ready-to-eat products. This product was founded by Mohamad Arif Azami in 2019. The first product for Salted Egg Cornflakes is known as The original one. It started in the Sungai Buloh, Selangor which is where the idea comes when the recipe is mixed with certain ingredients to make a delicious combination. In the beginning, only 1 flavour was released and packed in a bottle. The product was responded very well by customers. After that, they released a brand new flavour which is Spicy Salted Egg, Mini Popia Rangup and Hot and Spicy Maruku Ikan Bilis. They also promote their products on social media such as Facebook and Instagram as their main platform. To further expand the sales of these products, they are opening up space to agents and dropships. However, their sales did not get much response due to some problems. Especially, lack of graphic design in the advertisement, lack of knowledge in marketing, and inappropriate target audiences. As we all know, for small businesses to produce this ready-to-eat product uses a lot of capital, especially in production. However, the problem can be curbed if they analyse it more deeply and overcome the problem. There are many problems that Aductive can solve to improve their business to avoid losses, to compete with other competitors.